Growth hormone receptor antagonism downregulates ATP-binding cassette transporters contributing to improved drug efficacy against melanoma and hepatocarcinoma in vivo - Basu, Reetobrata; Qian, Yanrong; Mathes, Samuel; Terry, Joseph; Arnett, Nathan; Riddell, Trent; Stevens, Austin; Funk, Kevin; Bell, Stephen; Bokal, Zac; Batten, Courtney; Smith, Cole; et al. (Frontiers in Oncology, 2022)
Knockdown of GH receptor (GHR) in melanoma cells in vitro downregulates ATP-binding cassette-containing (ABC) transporters and sensitizes them to anti-cancer drug treatments. Here we aimed to determine whether a GHR antagonist (GHRA) could control cancer growth by sensitizing tumors to therapy through downregulation of ABC transporters in vivo. We intradermally inoculated Fluc-B16-F10 mouse melanoma cells into GHA mice, transgenic for a GHR antagonist (GHRA), and observed a marked reduction in tumor size, mass and tumoral GH signaling. Moreover, constitutive GHRA production in the transgenic mice significantly improved the response to cisplatin treatment by suppressing expression of multiple ABC transporters and sensitizing the tumors to the drug. We confirmed that presence of a GHRA and not a mere absence of GH is essential for this chemo-sensitizing effect using Fluc-B16-F10 allografts in GH knockout (GHKO) mice, where tumor growth was reduced relative to that in GH-sufficient controls but did not sensitize the tumor to cisplatin. We extended our investigation to hepatocellular carcinoma (HCC) using human HCC cells in vitro and a syngeneic mouse model of HCC with Hepa1-6 allografts in GHA mice. Gene expression analyses and drug-efflux assays confirm that blocking GH significantly suppresses the levels of ABC transporters and improves the efficacy of sorafenib towards almost complete tumor clearance. Human patient data for melanoma and HCC show that GHR RNA levels correlates with ABC transporter expression. Collectively, our results validate in vivo that combination of a GHRA with currently available anti-cancer therapies can be effective in attacking cancer drug resistance.